The Role of Schools in Instilling Religious Moderation Values: A Case Study at SMAN 1 Gantar, Indramayu (International Forum of Researchers and Lecturers, 2024)
This study examines the role of schools in internalizing religious moderation values among students, using SMAN 1 Gantar, Indramayu, as a case study. Religious moderation, emphasizing tolerance, respect for diversity, and peaceful coexistence, is crucial in Indonesia’s multicultural context. A quantitative survey method was employed, with data collected from 27 students through questionnaires, supported by interviews with school administrators and classroom observations. The findings reveal that most students demonstrate high levels of knowledge and positive attitudes toward religious moderation, though participation in related activities remains inconsistent. The integration of religious moderation values into the curriculum is moderate, suggesting room for further development. Challenges identified include limited student engagement and a lack of resources and structured teacher training. Despite these challenges, the study highlights the significant potential of schools to foster inclusivity and harmony. The results offer valuable insights for educators and policymakers seeking to enhance the role of education in promoting religious moderation. Future research should explore diverse settings and assess the long-term impact of educational interventions.